2020
DOI: 10.1097/rhu.0000000000001637
|View full text |Cite
|
Sign up to set email alerts
|

Does Age at Onset Affect the Clinical Presentation of Familial Mediterranean Fever in Children?

Abstract: Background/ObjectiveThe aim of this study was to compare the clinical and demographic features and evaluate the phenotypic and genotypic differences of pediatric familial Mediterranean fever (FMF) patients according to their age at disease onset.MethodsRecords of 854 patients who were diagnosed with FMF between 2006 and 2017 were evaluated. Patients were divided into 2 subgroups according to their age at disease onset. Group 1 comprised FMF patients who had experienced their first attack at 2 years or younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(47 reference statements)
1
8
1
Order By: Relevance
“…Although this study was conducted in only one region in Turkey, in agreement with other studies, homozygous M694V mutation was the most frequent. However, in our study, the rate of patients with this mutation was found to be higher than those reported in other Turkish studies 17,22 . This situation may be explained by the fact that consanguineous marriage is more frequent in the region.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Although this study was conducted in only one region in Turkey, in agreement with other studies, homozygous M694V mutation was the most frequent. However, in our study, the rate of patients with this mutation was found to be higher than those reported in other Turkish studies 17,22 . This situation may be explained by the fact that consanguineous marriage is more frequent in the region.…”
Section: Discussioncontrasting
confidence: 86%
“…The rates of arthritis and ELE in patients with M694V homozygous mutations were found to be significantly higher than the other patients ( P = 0.002 and <0.001, respectively). These results confirmed once again that M694V mutations are seen more frequently in FMF patients with musculoskeletal involvement such as arthritis and ELE 17,19,22,24 . In this sense, it may also be interpreted that our study did not agree with the results of the study from Japan which reported that musculoskeletal system findings are seen in FMF patients with later onset and a milder course 25 .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…To the best of our knowledge, concurrence of FMF and CNO has not been reported in case series on both conditions published so far 9,12–17 . There are some case reports in which FMF and CNO coexist in patients of different ethnic origin 26–30 . Three of them were Turkish patients, one of them was a Jewish patient from Canada, one of them was from Japan, and the other one was an Arabic patient from Qatar.…”
Section: Discussionmentioning
confidence: 91%
“…Patients with homozygous M694V and M680I mutations generally have a worse phenotype. Arthritis, renal amyloidosis and erysipelas‐like erythema have been more frequently reported in individuals with M694V homozygous mutation 5,6 …”
Section: Introductionmentioning
confidence: 99%